Formal Analysis Tools for the Synchronous Aspect Language Larissa. (20th November 2008) - Stauch, David
Abstract : We present two tools for the formal analysis of the aspect language Larissa, which extends the simple synchronous language Argos. The first tool concerns the combination of design-by-contract with Larissa aspects, and shows how we can apply an aspect not only to a program, but to a specification of programs in form of a contract, and obtain a new contract. The second concerns aspect interferences, that is, aspects that influence each other in an unintended way if they are applied to the same program. We present a way to weave aspects in a less conflict-prone manner, and a means to detect remaining conflicts statically. These tools are quite powerful, compared to those available for other aspect languages.